Pemanfaatan Teknologi dalam Pembelajaran melalui Pelatihan Penggunaan Aplikasi Pembelajaran melalui Canva untuk Siswa - Makmur, Elfira; Sa’ban Miru, Alimuddin; Wahyudi, Wahyudi; Shridivia Nuran, Andi; swal Burhan, Muh (Jurusan Pendidikan Teknik Elektro, 2025)
This Community Service Program (PKM) aims to enhance students’ abilities in utilizing educational technology through training on the use of the Canva application. The program was conducted at SMP Negeri 51 Makassar, located in Tamangapa District, Makassar City. Preliminary observations indicated that most students were not yet familiar with using digital design applications as learning media, particularly in the Information and Communication Technology (ICT) subject. The implementation method consisted of five stages: planning, socialization, training, mentoring, and evaluation. The activity involved 30 students who were trained to create posters, infographics, and learning presentations using Canva. The results showed significant improvement in students’ digital skills, with 90% of participants successfully producing their own learning media designs. In addition, teachers gained new insights into the use of design-based educational technology. This PKM activity had a positive impact on improving students’ digital literacy, creativity, and learning motivation, while also strengthening collaboration between Universitas Negeri Makassar and SMP Negeri 51 Makassar in promoting technology-based learning in the digital era.